The effect of sambiloto leaf (Andrographis paniculata Nees) extract inhibitor concentration on the corrosion rate of iron in the corrosive HCl medium and well water - Febriyandhi Yahya; Ade Trisnawati; Mohammad Arfi Setiawan (Jurnal Pijar Mipa, 2023)
Corrosion is a chemical reaction between metal and chemical substances in free air influenced by typographical conditions, climate, and humidity levels around the metal object. If left unchecked, it can cause damage to the metal infrastructure, material losses, and harm in terms of safety and security. Therefore, a way to inhibit corrosion is needed by creating an environmentally friendly inhibitor from natural materials. One of them is by utilizing Sambiloti leaf as a natural inhibitor. Sambiloto leaves contain tannins which can inhibit corrosion well. This study aimed to determine the efficiency of Sambiloto leaves ethanol extract in inhibiting the corrosion rate of metals in the corrosive medium of well water. HCl was soaked for seven days to determine the correlation between the corrosion rate and extract concentration in different corrosive media. Sambiloto leaves were extracted using the soxhletation method using 96% ethanol solution, then distilled to obtain a pure extract. Sambiloto leaf extract was then varied in concentration, namely 1%, 5%, 10%, and 15%. The corrosive medium is well water and HCl, and the metal material used is nails. The results showed that adding Sambiloto extract with a concentration of 15% in both corrosive mediums had the highest inhibitor efficiency values, namely 97.32% in the corrosive HCl medium and 69.3% in the corrosive well water medium. The results of the regression analysis showed that the addition of Sambiloto extract had a significant effect on the corrosion rate in well water media. In contrast, in the HCl medium, the addition of Sambiloto extract did not significantly affect the corrosion rate.